Correlation between Physical and Chemical Indoor Air Quality with Respiratory Health - Sudarmaji; Donny Ardyan; Fitri Anisai Rohmah; Novi Dian Arfiani; Dayinta Annisa Syaiful (Universitas Airlangga, 2026)
Introduction: Indoor air quality (IAQ) refers to the quality of air within enclosed spaces, which makes up most of the air inhaled daily. Pneumonia is reported to be 17.33 times more common in children living in unhealthy households than those in healthy homes. This study examined the relationship between physical and chemical indoor air quality and children's respiratory health in the working area of the South Krembangan Community Health Center in Krembangan Subdistrict, Surabaya City. Methods: This study employed an analytical observational design utilizing a case-control approach. Samples were selected through purposive sampling. A total of 54 respondents participated in this study, consisting of 27 cases and 27 controls. Results and Discussion: The findings demonstrated a strong correlation between the prevalence of pneumonia in children and air quality parameters including room temperature, humidity, PM2.5 concentration, lighting intensity, and ventilation area. Room temperature (p = 0.029), humidity (p = 0.049), PM2.5 (p = 0.014), lighting intensity (p = 0.006), and ventilation area (p = 0.028) all showed statistically significant correlations. Formaldehyde (HCHO), on the other hand, did not significantly correlate with the incidence of pneumonia (p = 0.569). Additionally, total volatile organic compounds (TVOCs) and carbon monoxide (CO) were found to be below the Environmental Health Quality Standards. Conclusion: Although many housing conditions already fulfil established criteria, it is advised that factors potentially affecting indoor air quality be taken into consideration.